Does the number of 6-monthly adjuvant zoledronate infusions received affect treatment efficacy for early breast cancer? A sub-study of ABCSG-12. (February 2023) - Beltran-Bless, Ana-Alicia; Clemons, Mark J.; Fesl, Christian; Greil, Richard; Pond, Gregory R.; Balic, Marija; Vandermeer, Lisa; Bjelic-Radisic, Vesna; Singer, Christian F.; Steger, Guenther G.; Helfgott, Ruth; Egle, Daniel; et al.
Abstract: Background: The widespread adoption of adjuvant bisphosphonate therapy for postmenopausal early breast cancer (EBC) patients was based on results of the Early Breast Cancer Trialist Group (EBCTCG) meta-analysis. Despite multiple regimens evaluated, there was no signal of varying efficacy with type, dose/dose intensity of bisphosphonate administration. We evaluated the effect of early treatment cessation using long-term outcome data from the ABCSG-12 trial. Patients and methods: ABCSG-12 randomized 1803 hormone-receptor positive EBC patients on ovarian suppression between 1999 and 2006 to receive 4 mg zoledronic acid 6-monthly or not (and tamoxifen or anastrozole, 2:2 factorial design). In the current study, we evaluated whether the number of zoledronate infusions had an impact on breast cancer-specific outcomes. We hypothesized that amongst patients who received at least one zoledronate infusion, the number of infusions had no effect on outcomes. Time-to-event endpoints were analysed with Cox models and Kaplan Meier curves starting from a 3-year landmark. BMD analysis was restricted to patients who participated in the BMD sub-study. Results: 725 patients who received at least one zoledronate infusion were included in the time-to-event analysis. There was no statistically significant difference in disease-free or overall survival in the patients who received ≤6 zoledronate infusions (n = 170) compared to those who received ≥7 zoledronate infusions (n = 555). Conclusions: Comparable to efforts to de-escalate treatment duration in metastatic bone disease, there was no evidence to indicate that a reduced number of zoledronate infusions is associated with reduced adjuvant efficacy. Further studies to define optimal regimens of adjuvant bone-targeted therapies are required. Highlights: Optimal adjuvant bisphosphonate dose and duration in breast cancer is unclear. We evaluated outcomes of early treatment cessation in the ABCSG-12 dataset. Receiving fewer than 7 zoledronate infusions had no significant effect on DFS or OS. Adjuvant bisphosphonate de-escalation in breast cancer must be further studied.